2018
DOI: 10.26710/jafee.v4i1.345
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Reaction to Election Cycles: The Nigerian Experience

Abstract: This study seeks to unravel the relationship between national electoral events and industry's stock market returns using the various presidential elections in Nigeria. The study adopts the traditional Market Model (MM) and testing with the Cumulative Abnormal Return (CAR) approach on the daily market data from the Nigerian Stock Exchange. Evidences abound that banking and Petroleum sector decreases before and increases after all elections. With the same trend for other sectors such as Conglomerates stock price… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In contrast, Osamwonyi and Omorokunwa (2017) find evidence of a negative effect on stock prices of selected companies around the presidential elections that were held in 2003, 2007and 2011. In another study, Osuala et al (2018 found that the 2015 Nigerian presidential election exerted a positive but insignificant impact on stock market performance, while Eboigbe and Modugu (2018) discover that industry stock returns tend to decline before then increase after the 1999, 2003, 2007 and 2011 elections. Scholars have long recognized the potential influence that psychological and social factors have on stock markets. For example, Lucey and Dowling (2005, p. 225) noted that "widely experienced fluctuations in social moods influence equity returns, with positive social feelings resulting in optimistic/higher equity pricing and negative social feelings resulting in pessimistic/lower equity pricing".…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, Osamwonyi and Omorokunwa (2017) find evidence of a negative effect on stock prices of selected companies around the presidential elections that were held in 2003, 2007and 2011. In another study, Osuala et al (2018 found that the 2015 Nigerian presidential election exerted a positive but insignificant impact on stock market performance, while Eboigbe and Modugu (2018) discover that industry stock returns tend to decline before then increase after the 1999, 2003, 2007 and 2011 elections. Scholars have long recognized the potential influence that psychological and social factors have on stock markets. For example, Lucey and Dowling (2005, p. 225) noted that "widely experienced fluctuations in social moods influence equity returns, with positive social feelings resulting in optimistic/higher equity pricing and negative social feelings resulting in pessimistic/lower equity pricing".…”
Section: Literature Reviewmentioning
confidence: 97%
“…In another study, Osuala et al . (2018) found that the 2015 Nigerian presidential election exerted a positive but insignificant impact on stock market performance, while Eboigbe and Modugu (2018) discover that industry stock returns tend to decline before then increase after the 1999, 2003, 2007 and 2011 elections.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Nigeria, Edoigbe and Modugu (2018) find evidence inconsistent with the opportunistic political business cycle theory . This study reveals that sector stock returns decreases before political elections and begin to rise after the election.…”
Section: Literature Reviewmentioning
confidence: 81%
“…A sectoral analysis of the presidential election effect on investor herding behaviour is necessary because whilst some sectors may be adversely affected by presidential elections, other sectors may be insulated from the effects of presidential elections. Edoigbe and Modugu (2018) opine that stocks of companies in different sectors react differently to presidential elections.…”
Section: Introductionmentioning
confidence: 99%